A Comparison of Methods for Analyzing Criminological Panel Data - Phillips, Julie A. (Journal of quantitative criminology, 2008)
We demonstrate that fixed- and random-effects models for pooled cross-sectional and time series data, and latent growth curve models for panel data are special cases of a more general model. We compare the estimates obtained from each type of model for a data set consisting of homicide rates and a vector of explanatory variables for 400 US counties over a 15-year period. Most, but not all, estimates are similar in the two models. We identify circumstances under which one approach may be advantageous to the other.